2017
DOI: 10.1097/aap.0000000000000652
|View full text |Cite
|
Sign up to set email alerts
|

Cadaveric Study of the Articular Branches of the Shoulder Joint

Abstract: Articular branches from the SN, AN, and LPN were identified. Articular branches of the SN and AN insert into the capsule overlying the glenohumeral joint posteriorly. Articular branches of the LPN exist and innervate a portion of the anterior shoulder joint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 21 publications
1
38
0
2
Order By: Relevance
“…Gardner7 was the first to report the innervation of GHJ from all four articular branches (SSN, AN, LPN and NS) 7. More recently, Nasu et al 14 found an articular branch terminating in the transverse humeral ligament that originated from the anterior division of AN,14 and Eckmann et al 16 found additional articular branches from SSN that coursed along the superior border of the spine of scapula to supply the posterosuperior GHJ capsule 16. However, in the current study, branches of the musculocutaeneous nerve reported by Wrete (1948) were not found 8…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gardner7 was the first to report the innervation of GHJ from all four articular branches (SSN, AN, LPN and NS) 7. More recently, Nasu et al 14 found an articular branch terminating in the transverse humeral ligament that originated from the anterior division of AN,14 and Eckmann et al 16 found additional articular branches from SSN that coursed along the superior border of the spine of scapula to supply the posterosuperior GHJ capsule 16. However, in the current study, branches of the musculocutaeneous nerve reported by Wrete (1948) were not found 8…”
Section: Discussionmentioning
confidence: 99%
“…The key landmarks identified include the coracoid process, midpoint between the suprascapular and spinoglenoid notches, rim of the anterior glenoid fossa, and acromial branch of the thoracoacromial artery. In previous studies, Nam et al 15 reported the course of the articular branch from LPN in relation to the coracoid process and coracoclavicular ligament,15 and Eckmann et al 16 related the articular branches of SSN, LPN and AN to the spine of scapula, thoracoacromial artery and head of humerus, respectively 16…”
Section: Discussionmentioning
confidence: 99%
“…Alternative regional analgesic techniques to interscalene brachial plexus block target the peripheral nerves that innervate the shoulder and may have a better side-effect profile [13]. The suprascapular and axillary nerves provide sensory innervation to most of the glenohumeral joint [14][15][16]. Therefore, a combined suprascapular and axillary nerve block is a valid alternative to interscalene brachial plexus block [4] with less impact on respiratory function [17][18][19][20][21][22] and hand-grip strength [23].…”
Section: Introductionmentioning
confidence: 99%
“…15 MHz, X-Porte, Fujifilm SonositeVR, Inc., Bothell, WA, USA) was applied to the side of the neck in a transverse plane to visualise the brachial plexus. The probe was then moved distally in order to identify the emergence of the suprascapular nerve from the superior trunk.…”
mentioning
confidence: 99%
“…More exact targeting may now be possible in light of this detailed mapping, as depicted in Figure 4 of the study of Eckmann et al 2 Their anatomical work shows us where sensory nerves can be safely targeted by dividing potential sites into zones. The sought-after clinical benefit of this precision involves avoidance of disrupting motor nerves, as well as sensory pathways not implicated in the patient's pain syndrome.…”
mentioning
confidence: 99%